KEBUTUHAN PELAYANAN SOSIAL BAGI KORBAN BENCANA ALAM DI PROPINSI SUMATERA BARAT - Gunawan Gunawan (Puslitbangkesos Kementerian Sosial RI, 2009)
Case studies in West Sumatra Province, aims to explore the information about the needs of social services for victims of natural disasters. Data and information were collected by interviews and obsen1ation. Results of descriptive analysis of data and information collected, revealed that the public has to know information about neighborhood conditions, which were categorized as natural disaster-prone areas, communities have a habit in the face of natural disasters ranging from the rescue, response emergency, until the recoven; period. However, every time a disaster is always high risk and long recovery. Given the Earthquake in West Sumatra is not an incidental event (rare), then the service is not enough Victims limited emergency services, recovery, empowerment and protection, but the social services necessary to improve communitty preparedness. Activities services to victims of natural disasters can be grouped into 3 periods, namely: shortterm; Medium Term; Long Term.